2013
DOI: 10.1002/mds.25664
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in early Parkinson's disease: The impact of nonmotor symptoms

Abstract: Nonmotor symptoms (NMS) are common in patients with established Parkinson's disease (PD) and have a major impact upon quality of life. We investigated the significance of NMS in relation to health-related quality of life (HRQoL) in patients with newly diagnosed PD. Patients and healthy controls were recruited as part of the Incidence of Cognitive Impairment in Cohorts with Longitudinal Evaluation in Parkinson's Disease Study. Prevalence of NMS was determined with the Non-Motor Symptom Questionnaire. HRQoL was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
211
4
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(251 citation statements)
references
References 48 publications
18
211
4
10
Order By: Relevance
“…We anticipated worse mobility in the older PD-20 group, but their motor performance is likely an integral link to their survival. Also, the absence of a difference in mobility could explain why the QoL and caregiver burden was similar for the two subgroups, as impaired gait impacts QoL [25]. Those younger than age 70 had significantly higher rates of DBS treatment, which is not surprising given the risks of DBS surgery increase in those above age 70.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipated worse mobility in the older PD-20 group, but their motor performance is likely an integral link to their survival. Also, the absence of a difference in mobility could explain why the QoL and caregiver burden was similar for the two subgroups, as impaired gait impacts QoL [25]. Those younger than age 70 had significantly higher rates of DBS treatment, which is not surprising given the risks of DBS surgery increase in those above age 70.…”
Section: Discussionmentioning
confidence: 99%
“…11 As the disease progresses, a collage of motor, affective, and behavioral symptoms often leads to considerably reduced HRQOL for many with PD. 12 Mood disorders, impaired cognition, and sleep patterns worsen, which contribute to increased stress and social isolation over time. 13,14 HRQOL is particularly affected by depression, which is comorbid with PD in nearly half of those affected by the disease.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Duncan et al showed that sleep disturbances have a significant impact on health-related quality of life assessments warranting intervention. 44 Interventions are largely dependent on the underlying etiology of the patient's sleep disturbance. 45 For instance, if a patient complains of insomnia, possible etiologies to consider in addition to natural disease progression include side effects associated with the patient's PD medications, and concurrent nonmotor symptoms, such as pain, urinary issues, depression, hallucinations, and psychosis that can disrupt sleep.…”
Section: Sleep Disordersmentioning
confidence: 99%